Life Balance: How to Convert Professional Success into Personal HappinessLife Balance: How to Convert Professional Success into Personal Happiness, by Weiss Alan. San Francisco: Jossey-Bass/Pfeiffer, 2003. - Allen, Tammy D. (Academy of Management Review, 2005)
A review is presented of the book ?Life Balance: How to Convert Professional Success Into Personal Happiness,? by Alan Weiss.